Expanding the horizon for breast cancer screening in India through artificial intelligent technologies -A mini-review - Bhattacharya, Sudip; Varshney, Saurabh; Heidler, Petra; Tripathi, Shailesh K. (Frontiers in Digital Health, 2022)
Breast cancer claims the lives of 500000 women each year globally. In India, the annual prevalence is roughly 75000.Breast cancer deaths are higher in rural locations than in metropolitan areas due to multiple reasons like delay in diagnosis, cost of treatment, cultural factors and many more. Breast cancer is the most common cancer among Indian women, with an incidence of 25.8 per 100,000 women according to the Ministry of Health and Family Welfare. Late detection is responsible for poor quality of life (QOL), and it is the leading cause of death. In metropolitan regions, one in every 22 women will have breast cancer over their lifetime; but in rural areas, one in every 60 women will develop the illness. In this paper we have discussed how emerging artificial intelligent technologies namely “Niramai”, "iBreastExam,” “MammoAssist” are emerging as an hope for early detection by screening in resource poor settings in turn, which can improve the QOL among breast cancer patients.